Rancang Bangun E-Learning Pelajaran Pilihan Pada SMAN 3 Palangkaraya Berbasis Web (Studi Kasus Pelajaran Bahasa Jerman): Web-Based Design And Design Of E-Learning Optional Lessons At SMAN 3 Palangkaraya (German Language Lesson Case Study) - Sam'ani, Sam'ani; Haris, Ferdiyani; Suparno, Suparno; Ichsan, Mochammad; Qamaruzzaman, Muhammad Haris; Yana, Priska (Jurnal Sains Komputer dan Teknologi Informasi, 2023)
The current development of Information Technology makes it easier for people to access information anytime and anywhere, making distance not an obstacle to getting information from various corners of the world. Therefore, mastery of a foreign language other than English is important. One of the foreign languages ​​that has an important role is German, so German language subjects are currently one of the foreign language subjects besides English taught in both SMA, MA and SMK. Using e-Learning makes it possible for the educational process to take place without face-to-face contact and the development of knowledge for students can be done easily. The problem of this research is how to build a Web-Based German e-Learning Application at SMA Negeri 3 Palangkaraya. This application aims to make it easy for students to be able to access German language learning materials wherever they want to access them when connected to the internet network, so that it can encourage students' interest in learning German. The application that will be created is web-based using the PHP programming language with a MySQL database and utilizing tools in web programming, namely bootstrap, which is used to create a website page that supports all kinds of devices. The software development method used is the waterfall model which includes the stages of system/information engineering, analysis, design, implementation (coding), testing and maintenance.